FIRST KOMATIITE FIND IN THE EASTERN SAYAN - Mekhonoshin A.S.; Sesk'ko A.I. (My University, 1988)
Ultramafic rocks in the Precambrian sequence of the Eastern Sayan were traditionally classified as plutonic. Within the Khan-Ashkasok synclinorial trough of Early Proterozoic age studied by us, such rocks were mapped as two dunite-peridotite-serpentinite lenses and included in the Aktovrak intrusive complex of Paleozoic age. However, further study showed that these rocks are volcanic in origin. On the northeast the Khan-Ashkasok trough abuts the East Sayan block of Late Archean age and, on the southwest, is bounded by the Caledonides of Tuva. Ultramafic rocks of the Khangorok group are confidently classified as komatiites. The seven komatiite flows exposed here are interbedded with tholeiitic metabasalt and metarhyolite and are similar to them petrochemically and geochemically.
Keywords: Archean; Paleozoic; Precambrian; Proterozoic; Докембрий; Докембрий::Протерозой; Докембрий::Архей; Precambrian; Paleozoic; Precambrian::Proterozoic; Precambrian::Archean; Палеозой